2019
DOI: 10.1002/mgg3.927
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal tumors in neurofibromatosis 1 with special reference to fatal gastrointestinal stromal tumors (GIST)

Abstract: Background Type 1 neurofibromatosis (NF1) is a genetic tumor predisposing Rasopathy. NF1 patients have an increased risk for developing benign and malignant tumors, but the occurrence of intestinal tumors has not been investigated at the population level. Methods In this retrospective register‐based total population study, diagnoses of gastrointestinal tract tumors were retrieved from the Finnish Care Register for Health Care for 1,410 NF1 patients and 14,030 reference persons. We also reviewed the death certi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Type 1 Neurofibromatosis (NF1, von Recklinghausen disease) is an autosomal and dominant disorder caused by the inactivation of the NF1 gene on chromosome 17, which is a tumour suppressor gene in some cell types, encoding the neurofibromin protein, a member of the RAS family [ [21] , [22] , [23] , [24] , [25] ]. This condition is characterised by cutaneous neurofibromas, café au lait macules, axillary and inguinal freckling, and Lish nodules.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Type 1 Neurofibromatosis (NF1, von Recklinghausen disease) is an autosomal and dominant disorder caused by the inactivation of the NF1 gene on chromosome 17, which is a tumour suppressor gene in some cell types, encoding the neurofibromin protein, a member of the RAS family [ [21] , [22] , [23] , [24] , [25] ]. This condition is characterised by cutaneous neurofibromas, café au lait macules, axillary and inguinal freckling, and Lish nodules.…”
Section: Discussionmentioning
confidence: 99%
“…NF1 is associated with several tumours, including those of the GI tract, and GISTs are indicated as the most commonly GI NF1 associated tumours [ 25 , 26 ]. The incidence of GIST in the NF1 population is estimated to be markedly higher compared to that of the general population [ [22] , [23] , [24] ], although the frequency of NF1 GIST varies greatly in the literature, ranging from 5% to 29% [ 24 , 27 , 28 ]. Levy et al [ 29 ] showed, significantly, in four out of five (80%) patients with multiple lesions, only one tumour was identified on preoperative CT scan, a finding reflected in our case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the general population, the incidence of MPNSTs starts to increase already at teenage in NF1, and the standardized incidence ratio of MPNST in NF1 may be as high as 2,056 (95% CI 1,561–2,658) (Uusitalo et al, 2016; Peltonen et al, 2019). In addition to tumors of the nervous system and brain, other cancers associated with NF1 include, for example, those of the breast and gastrointestinal tract (Sharif et al, 2007; Uusitalo et al, 2016; Seminog and Goldacre, 2013; Ylä‐Outinen et al, 2019; Kenborg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%